When the Beautiful IS the Good: Towards Linguistic Revealing and the Fitting Order of Ethos in T.S Eliot’s “Four Quartets” - Hansali, Omar (International Journal of Language and Literary Studies, 2024)
Outside the politics of environmental justice which imbue the world with false responsibility, the ontology of technological subjectivity masks a drive to deplete and subjugate. The question then becomes: how is it possible to be ecologically just knowing that nature is conceived as an organism? More so, how can language be ethically restorative whilst the relationship between the ‘word’ and the ‘thing’ is grounded on the logic of representation? The palimpsest of ontological subjectivity, arising from Platonic eidos and cascading to Nietzsche’s will to power, reproduces a hierarchical system. The purpose of this study is to administer a trenchant critique of ontology rather than merely engage in ecological compassion and political power games. This essay defends the argument that the poetic realm preserves the long-forgotten essence of nature as physis, chiefly as that which evades the technological worldview of objectification. Instead of locating the salvation of nature in the subjectivity of the romantic lyricist or the ecological moralist, dwelling poetically demands a form of linguistic revealing and an ethos of response that lets nature be. First, Eliot’s image of the ‘matrimonie’ allows earth to appear as a gathering force. Second, the ‘river’ gathers the ‘land’s edge’ and the ‘gods’ radiance’ around the precinct of natural guardianship. It so happens that Eliot’s depiction of nature exhorts human beings to live amid the sprouting of trees, the supporting of soil, and the streaming of the river. This restorative act advocates an incisive critique of technological logic and an avowal of meditative thinking.